Failure analysis and prevention - Becker, William T.; Shipley, Roch J. (ASM International, 2002)
"Volume 11 describes the principles, practices, and analytical techniques of failure analysis. It provides information on life assessment and manufacturing operations, examining the causes, mechanisms, and appearances of common failure modes, including fracture, corrosion, wear, and distortion. It also discusses general engineering considerations associated with failure prevention, covering fundamental root causes, materials selection, and the role of design reviews in prevention and analysis."-- ASM Handbooks Online website, viewed on April 21, 2022.
"Includes articles from the Section 'Failures of Manufactured Components and Assemblies' in 'Metals Handbook,' 9th Edition, Volume 11, 'Failure Analysis and Prevention,' 1986, p 457-727. The articles in this Section were not updated for the 2002 edition. The article 'Why Tools and Dies Fail' was added as an online update in 2016."--Publication history page, viewed online on April 21, 2022.
Keywords: Metals -- Fractures -- Handbooks, manuals, etc.; Metal-work -- Handbooks, manuals, etc.; Failure analysis (Engineering) -- Handbooks, manuals, etc.; Metals -- Handbooks, manuals, etc.; Metals -- Fracture.; elektronické knihy; electronic books